(untitled) (Research, Society and Development, 2024)
Autoimmune diseases progressively impact the population’s quality of life and are considered a factor of public health care. Among the most diverse autoimmune diseases, lupus in its different forms has stood out as a pathology that affects individuals, predominantly affecting women in different life cycles. Systemic lupus erythematosus (SLE) is an autoimmune disease, marked by periods of remission and activity, affecting one or more organs and tissues of the body, resulting in inflammation and damage. Risk factors for the disease are related to lifestyle, including issues such as stress, physical activity, diet, among others. The aim of this study was to evaluate the influence of diet on adults with autoimmune diseases with systemic lupus. The methodology was carried out through a literature review based on scientific articles from the last ten years, found in academic sources: Pubmed, Google Scholar, SciELO and CAPES, including articles in Portuguese and English. As final considerations, it is noteworthy that scientific evidence is consistent with the relationship between the influence of nutrition as one of the pillars in disease management, which is one of the main non-pharmacological factors used to maintain adequate nutritional status and prevent possible associated complications. Furthermore, the need for more studies focused on the influence and importance of nutrition for patients with autoimmune diseases is emphasized.